2016
DOI: 10.1016/j.jpor.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of low-intensity pulsed ultrasound on wound healing using scratch assay in epithelial cells

Abstract: LIPUS exposure promotes wound closure in the scratch assay and up-regulates the expression level of integrin α6β4 as compared with the control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…We analyzed the expression of these two markers and found that an increase of E‐Cadherin and a decrease of Vimentin are induced by LIPUS treatment, thus suggesting their ability to halt the EMT process or, vice versa, to favor the mesenchymal to epithelial transition (MET; 1,000 kHz, p ≤ .01; 4500 kHz, p ≤ .01 for E‐Cadherin in HT29; 1000 kHz, p ≤ .05; 4,500 kHz, p ≤ .05 for E‐Cadherin in Caco2; 1,000 kHz, p ≤ .01; 4,500 kHz, p ≤ .01 for Vimentin in HT29; 1000 kHz, p ≤ .05; 4,500 kHz, p ≤ .01 for Vimentin in Caco2 (Figure 5a,b). LIPUS has been reported to shorten the time required for wound healing in gingival epithelial cells (Iwanabe et al, 2016). Here, we tested the effects of LIPUS on wound healing closure in both colorectal cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the expression of these two markers and found that an increase of E‐Cadherin and a decrease of Vimentin are induced by LIPUS treatment, thus suggesting their ability to halt the EMT process or, vice versa, to favor the mesenchymal to epithelial transition (MET; 1,000 kHz, p ≤ .01; 4500 kHz, p ≤ .01 for E‐Cadherin in HT29; 1000 kHz, p ≤ .05; 4,500 kHz, p ≤ .05 for E‐Cadherin in Caco2; 1,000 kHz, p ≤ .01; 4,500 kHz, p ≤ .01 for Vimentin in HT29; 1000 kHz, p ≤ .05; 4,500 kHz, p ≤ .01 for Vimentin in Caco2 (Figure 5a,b). LIPUS has been reported to shorten the time required for wound healing in gingival epithelial cells (Iwanabe et al, 2016). Here, we tested the effects of LIPUS on wound healing closure in both colorectal cancer cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed the expression of these two markers and found that an increase of E-Cadherin and a decrease of Vimentin are induced by LIPUS treatment, thus suggesting their ability to halt the EMT process or, vice versa, to favor the mesenchymal to epithelial (Figure 5a,b). LIPUS has been reported to shorten the time required for wound healing in gingival epithelial cells (Iwanabe et al, 2016).…”
Section: Us Alters Cell Viability and Clonogenicity Of Colon Cancermentioning
confidence: 99%
“…The LIPUS generating system with six individual ultrasound transducers was previously described3738. The culture plate was placed above these transducers with a thin layer of coupling gel3940. The wells vertically above the transducers were used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…LIPUS also stimulates the proliferation of induced pluripotent stem cell-derived neural crest stem cells (iPSC–NCSC) [ 33 ]. The proliferative capacity of other cell types, including osteoblasts [ 34 ] and epithelial cells [ 35 ], is also enhanced by LIUS, indicating that this is likely a general phenomenon.…”
Section: Biological Effects Of Ultrasoundmentioning
confidence: 99%